Comparison of genetic and immunological responses to tick infestation between three breeds of sheep in South Africa - Thutwa, Ketshephaone (University of the Free State, 2016)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 The study investigated genetic parameters and immunological responses to tick infestation in three South African sheep breeds (Namaqua Afrikaner [NA], Dorper and SA Mutton Merino [SAMM]). The study aimed to estimate genetic and crossbreeding parameters for tick count (TC) and weaning weight (WW), to examine the histology of tick attachment and control sites, to select reference genes for normalizing gene expression data in this study, to compare cytokines gene expression at tick attachment and control sites and finally to compare cutaneous hypersensitivity reactions to unfed larvae extracts (ULE) of Rhipicephalus evertsi evertsi between NA, Dorper and SAMM sheep. Genetic parameters for WW and TC were estimated using data of lambs maintained on the Nortier Research Farm from 2010 to 2015. Firstly, data of purebred commercial Dorper and SAMM lambs were combined with data of their reciprocal crosses to assess breed effects and the possible effect of non-additive genetic variation on WW and TC. In the second analysis, data of purebred commercial Dorper lambs were combined with data of the unimproved, indigenous NA and the NA x Dorper cross. In Analysis 1 the coefficient of variations (CV) were 24%, 95% and 50% for WW, untransformed total TC and square root transformed total TC, respectively. Genotype affected WW but not TC. A heterosis estimate of approximately 4% was derived for WW. A single-trait h² estimate for TC was 0.11±0.09. A model analysing across-genotype h² yielded a slightly lower h² estimate of 0.08 ± 0.07. In Analysis 2 the CV were 27% and 55% for WW and square root transformed total TC, respectively. WW and TC were affected by genotype. WW exhibited heterosis amounting to 8.5% while the corresponding value for TC amounted to -23%. The single-trait h² estimate for TC was 0.06±0.05. A model analysing across-genotype h² yielded a substantially higher h² estimate of 0.27±0.07. These results suggest that genetic variation in TC was primarily associated with differences among genetic groups while differences between individual animals within genetic groups were not as important. Heterosis estimates for WW were variable between two analyses, but within ranges reported in the literature. This study established significant variation in TC between sheep genotypes when the indigenous NA breed formed part of the analysis. The NA x Dorper cross resembled the improved Dorper breed for WW but the unimproved, resistant NA for TC and exhibited worthwhile levels of heterosis for both traits. Indigenous ovine genetic resources may be instrumental in providing genetic material for adaptive traits in environments susceptible to high levels of tick infestation. Further research is required to elucidate the role that adapted indigenous ovine genetic resources may play in an integrated tick management strategy under conditions characterised by high levels of tick challenge. A histological study was conducted to assess histological features at tick attachment and control sites in pure breeds. Skin biopsies were examined using routine histological techniques for immunological cell infiltration and skin reactions. Marked variation in immunological responses to tick attachment within and between sheep breeds was observed. There were differences between the attachment and control sites in most of the skin changes (defects) except for four skin defects in the NA. However, all breeds had similar frequencies of skin defects at tick attachment sites. Tick attachment sites were more likely to be infiltrated by cells within as well as across breeds. The NA and SAMM breeds tended to demonstrate greater cellular infiltrations of specific leukocytes at tick attachment sites compared to Dorpers. Basophils, mast cells and eosinophils were increasingly recruited at tick attachment site in NA ewes compared to the Dorper and, occasionally, the SAMM breeds. These results suggest the importance of these cells in sheep resistance to tick infestation. Tick genera influenced the recruitment of neutrophils to tick attachment sites. Tick gender, sampling site as well as tick engorgement level did not affect the number of immunological cells. Further studies should be done with one tick species at a time to better comprehend the species-specific impact of tick attachment to animals belonging to divergent sheep breeds. Five genes (18S, GAPDH, YWHAZ, B2M and SDHA) were tested for their stability. SDHA, YWHAZ and B2M were the most suitable reference genes recommended by geNorm analysis for normalizing gene expression data in sheep skin. These findings will assist in normalizing data in gene expression studies at tick attachment and control sites of the NA, Dorper and SAMM breeds. This study suggested that no reference gene is stably expressed in different experimental conditions. The expression of IL-1β, IL-8, CCL2 and CCL26 was quantified in real-time qPCR. IL-1β and IL-8 were more highly expressed at tick attachment than at control sites. NA ewes expressed IL-1β more at tick attachment sites than Dorpers. The NA breed was also more likely to upregulate the expression of the CCL2, CCL26 and IL-8 genes at tick attachment sites compared to control sites than the other breeds. This indicates that IL-1 β, CCL26 and IL-8 may play a part in resistance or susceptibility of sheep to tick infestation. The differences in expression of the two chemokines between the resistant NA and more susceptible SAMM and Dorper imply that the NA breed could be able to overcome the anti-chemokine activity of tick saliva. ULE of R. evertsi evertsi induced hypersensitivity reactions in all the breeds. The indigenous NA displayed stronger reactions, immediate and delayed, than the commercial breeds. The results suggest that cell-mediated immune responses are invoked to fight against tick infestation in the NA. The hypersensitivity reaction may be used as a phenotypic marker to select animals or breeds that are more resistant to tick infestation. It is well-known that challenge-based research for promoting resistance to pathogens is under scrutiny from an ethical and welfare perspective. The methods employed here could be refined to enable routine evaluation of valuable animals without resorting to more invasive strategies, such as allowing adequate natural challenge to accrue over time in selection candidates. Overall, the component studies reported in the thesis increased the present understanding of ovine tick-host interactions and factors contibuting to breed differences in tick loads. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die studie het genetiese parameters en immunologiese reaksies op bosluisbesmetting in drie Suid-Afrikaanse skaaprasse (Namakwa Afrikaner [NA], Dorper en SA Vleismerino [SAVM]) ondersoek. Die studie het ten doel gehad om genetiese en kruisteelparameters vir bosluistelling (BT) en speengewig (SG) te skat, om die histologie van bosluisaanhegting en kontroleterreine te ondersoek, om verwysingsgene vir normalisering van geenuitdrukkingdata in hierdie studie te selekteer, om sitokiene-geenuitdrukking by bosluisaanhegting en kontroleterreine te vergelyk en laastens om kutane hipersensitiwiteitsreaksies van ongevoede larwe-uittreksels (OLU) van Rhipicephalus evertsi evertsi tussen NA-, Dorper- en SAVM-skape te vergelyk. Genetiese parameters vir SG en BT is beraam met behulp van data van lammers wat vanaf 2010 tot 2015 op die Nortier Navorsingsplaas in stand gehou is. Eerstens is data van rasegte kommersiële Dorper- en SAVM-lammers gekombineer met data van hul wederkerige kruisings om ras-effekte en die moontlike effek van nie-additiewe genetiese variasie op SG en BT te bepaal. In die tweede ontleding is data van rasegte kommersiële Dorper-lammers gekombineer met data van die onverbeterde, inheemse NA- en die NA x Dorper-kruising. In Analise 1 is die koëffisiënt van variasies (KV) 24%, 95% en 50% vir SG, ongetransformeerde totale BT en vierkantswortel getransformeerde totale BT, onderskeidelik. Genotipe het SG aangetas, maar nie BT nie. 'n Heteroseskatting van ongeveer 4% is vir SG afgelei. ’n Enkel-eienskap h²-skatting vir BT was 0.11±0.09. ’n Model wat ’n kruis-genotipe h² ontleed het, het ’n effens laer h²-skatting van 0.08 ± 0.07 opgelewer. In Analise 2 was die KV onderskeidelik 27% en 55% vir SG en vierkantswortel getransformeerde totale BT. SG en BT is deur genotipe beïnvloed. SG het heterose getoon wat 8.5% beloop het terwyl die ooreenstemmende waarde vir BT -23% beloop het. Die enkel-eienskap h²-skatting vir BT was 0.06±0.05. 'n Model wat ’n kruis-genotipe h² ontleed het, het 'n aansienlik hoër h²-skatting van 0.27±0.07 opgelewer. Hierdie resultate dui daarop dat genetiese variasie in BT hoofsaaklik geassosieer is met verskille tussen genetiese groepe terwyl verskille tussen individuele diere binne genetiese groepe nie so belangrik was nie. Heterose skattings vir SG was veranderlik tussen twee ontledings, maar binne reekse wat in die literatuur gerapporteer is. Hierdie studie het beduidende variasie in BT tussen skaapgenotipes vasgestel wanneer die inheemse NA-ras deel van die analise gevorm het. Die NA x Dorper-kruising het soos die verbeterde Dorperras vir SG gelyk, maar die onverbeterde, weerstandbiedende NA vir BT het waardevolle vlakke van heterose vir beide eienskappe getoon. Inheemse skaap genetiese hulpbronne kan instrumenteel wees in die verskaffing van genetiese materiaal vir aanpasbare eienskappe in omgewings wat vatbaar is vir hoë vlakke van bosluisbesmetting. Verdere navorsing is nodig om die rol toe te lig wat aangepaste inheemse skaapgenetiese hulpbronne kan speel in 'n geïntegreerde bosluisbestuurstrategie onder toestande wat gekenmerk word deur hoë vlakke van bosluisuitdagings. 'n Histologiese studie is uitgevoer om histologiese kenmerke by bosluisaanhegting en beheerplekke in suiwer rasse te bepaal. Velbiopsies is ondersoek met behulp van roetine histologiese tegnieke vir immunologiese selinfiltrasie en velreaksies. Merkbare variasie in immunologiese reaksie op bosluisaanhegting binne en tussen skaaprasse is waargeneem. Daar was verskille tussen die aanhegtings- en kontroleplekke in meeste van die velveranderinge (defekte) behalwe vir vier veldefekte in die NA. Alle rasse het egter soortgelyke frekwensies van vel-defekte by bosluisaanhegtingsplekke gehad. Bosluisaanhegtingsplekke was meer geneig om deur selle binne sowel as oor rasse geïnfiltreer te word. Die NA- en SAVM-rasse was geneig om groter sellulêre infiltrasies van spesifieke leukosiete by bosluisaanhegtingsplekke te toon in vergelyking met Dorpers. Basofiele, mastselle en eosinofiele is toenemend by bosluisaanhegtingsplekke by NA-ooie aangetref in vergelyking met die Dorper-, en, af en toe, die SAVM-rasse. Hierdie resultate dui op die belangrikheid van hierdie selle in skaapweerstand teen bosluisbesmetting. Bosluisgenera het die behoefte aan neutrofiele by bosluisaanhegtingsplekke beïnvloed. Die bosluisgeslag, monsternemingsplek sowel as bosluis-bloedtoevoervlak het nie die aantal immunologiese selle beïnvloed nie. Verdere studies moet met een bosluisspesie op 'n slag gedoen word om die spesie-spesifieke impak van bosluisaanhegting aan diere wat aan uiteenlopende skaaprasse behoort, beter te begryp. Vyf gene (18S, GAPDH, YWHAZ, B2M en SDHA) is vir hul stabiliteit getoets. SDHA, YWHAZ en B2M was die mees geskikte verwysingsgene wat aanbeveel is deur geNorm analise vir normalisering van geenuitdrukking data in skaapvel. Hierdie bevindinge sal help met die normalisering van data in geenuitdrukkingstudies by bosluisaanhegting en kontroleplekke van die NA-, Dorper- en SAVM-rasse. Hierdie studie het voorgestel dat geen verwysingsgeen stabiel uitgedruk word in verskillende eksperimentele toestande nie. Die uitdrukking van IL-1β, IL-8, CCL2 en CCL26 is in intydse qPCR gekwantifiseer. Meer IL-1β en IL-8 is uitgedruk by bosluisaanhegting as by kontroleplekke. NA-ooie het IL-1β meer by bosluisaanhegtingsplekke uitgedruk as Dorpers. Die NA-ras was ook meer geneig om die uitdrukking van die CCL2-, CCL26- en IL-8-gene by bosluisaanhegtingsplekke opwaarts te reguleer in vergelyking met kontroleplekke as die ander rasse. Dit dui daarop dat IL-1 β, CCL26 en IL-8 'n rol kan speel in weerstand of vatbaarheid van skape vir bosluisbesmetting. Die verskille in uitdrukking van die twee chemokiene tussen die weerstandbiedende NA en meer vatbare SAVM en Dorper impliseer dat die NA-ras die anti-chemokien aktiwiteit van bosluis speeksel kan oorkom. ULE van R. evertsi evertsi het hipersensitiwiteitsreaksies in al die rasse veroorsaak. Die inheemse NA het sterker reaksies getoon, onmiddellik en vertraag, as die kommersiële rasse. Die resultate dui daarop dat sel-gemedieerde immuunreaksies ontketen word om teen bosluisbesmetting in die NA te veg. Die hipersensitiwiteitsreaksie kan as 'n fenotipiese merker gebruik word om diere of rasse te selekteer wat meer bestand teen bosluisbesmetting is. Dit is welbekend dat uitdagingsgebaseerde navorsing vir die bevordering van weerstand teen patogene vanuit 'n etiese en welsynsperspektief onder die loep geneem word. Die metodes wat hier aangewend word, kan verfyn word om roetine-evaluering van waardevolle diere moontlik te maak sonder om meer ingrypende strategieë te gebruik, soos om voldoende natuurlike uitdagings oor tyd toe te laat by seleksie-kandidate. Oor die algemeen het die komponentstudies wat in die tesis gerapporteer is, die huidige begrip van bosluis-gasheer-interaksies en faktore wat bydra tot teelverskille in bosluisladings verhoog. ___________________________________________________________________

𝑺𝒆𝑺𝒐𝒕𝒉𝒐 Diphuputso tsena di fuputsa mekgwa ya tshebetso ya dijini le masole a mmele tshwaetsong ya mefuta e meraro ya dinku tsa mona Afrika Borwa (Namaqua Afrikaner [NA], Dorper le SA Mutton Merino [SAMM]). Diphuputso tsena di reretswe ho lekanya mekgwa ya dijini le tswadiso bakeng sa bongata ba mekgasa (TC) le weaning weight (WW), e le ho hlahloba disele tsa mekgasa le sebaka sa taolo, ho kgetha dijini ho lokisa tshebetso ya dijini diphuputsong tsena, ho bapisa tshebetso ya dijini ya cytokines boemong ho longwa ke mekgasa le control sites mme qetellong ho be le papiso le tshebetso ya cutaneous hypersensitivity ho unfed larvae extracts (ULE) ya Rhipicephalus evertsi evertsi pakeng tsa dinku tsa NA, Dorper le SAMM. Mekgwa ya dijini bakeng sa WW le TC e ile ya lekanywa ka ho sebedisa dintlha tsa dikonyana tse bolokilweng Polasing ya Diphuputso ya Nortier ho tloha ka 2010 ho isa ka 2015. Tabeng ya pele, dintlha tsa tswadiso e tlwaelehileng ya mofuta o le mong wa dinku tsa Dorper le SAMM di kopantswe le dintlha tsa ditswadisano tsa tsona e le ho hlahloba ditlamorao tsa tswadiso le diphetho tse ka kgonehang tsa mefuta ya dijini ho WW le TC. Ho tshekatsheko ya bobedi, dintlha tsa tswadiso ya mofuta o le mong tsa kgwebo tsa dinku tsa Dorper di kopantswe le dintlha tsa NA le tswadiso ya NA x Dorper. Ho Tshekatsheko ya 1 coefficient of variations (CV) e ne e le 24%, 95% and 50% bakeng sa WW, untransformed total TC le square root ya TC, ka ho latelana. Genotype e amme WW empa eseng TC. Tekanyo ya heterosese e ka bang 4% e fumanwe bakeng sa WW. Tekanyo ya single-trait h² ka TC e ne e le 0.11±0.09. Mokgwa wa tshekatsheko ya across-genotype h² o hlahisitse tekanyo e ka tlase hanyenyane ho h² ya 0.08 ± 0.07. Ho tshekatsheko ya 2 CV e bile 27% le 55% bakeng sa WW le square root transformed total TC, ka ho latelana. WW le TC di amilwe ke genotype. WW e bontshitse heterosese e fihlang ho 8.5% ha boleng bo tsamaelanang le bona bakeng sa TC bo fihla ho -23%. Tekanyo ya single-trait h² bakeng sa TC e bile 0.06±0.05. Mokgwa wa tshekatsheko ya across-genotype h² o hlahisitse tekanyo e ka hodimo haholwanyane ya h² ya 0.27±0.07. Diphetho tsena di bontsha hore diphetoho tsa dijini ho TC di ne di amanywa haholo le diphetoho tsa dihlopha tsa dijini ha diphetoho pakeng tsa phoofolo ka nngwe ka hara sehlopha sa dijini di ne di se bohlokwa hakaalo. Ditekanyo tsa heterosese bakeng sa WW di ne di ka fetofetoha pakeng tsa ditshekatsheko tse pedi, empa ka hara dipehelo tse beilweng ka hara dingolwa. Diphuputso tsena di hlahisitse diphetoho tse kgolo tsa TC pakeng tsa mefuta ya dinku ha mofuta wa kgale wa NA e bile karolo ya tshekatsheko. Tswadiso ya NA x Dorper e futsitse mofuta o ntlafaditsweng wa Dorper bakeng sa WW empa eseng NA bakeng sa TC mme e totobaditse maemo a phahameng a heterosese bakeng sa mefuta ka bobedi. Mehlodi ya kgale ya dijini e ka sebediswa haholo bakeng sa ho fana ka thepa ya dijini bakeng sa makgabane a tshwano ditokolohong tse nang le maemo a phahameng a ho ata le ho longwa ke mekgasa. Ho hlokeha diphuputso tse ding tse tswetseng pele ho hlahisa seabo se ananetseng mehlodi ya kgale ya dijini bakeng sa bolaodi kapa phediso ya mekgasa tlasa maemo a hlaloswang ka hore a na le phephetso e kgolo ya mekgasa. Diphuputso tsa histoloji di ile tsa etswa ka ho hlahloba makgabane a histoloji nakong ya ho longwa ke mekgasa le dibaka tsa taolo ho ditswala tsa motheo. Ho ile ha hlahlojwa letlalo e leng skin biopsies ka ho sebedisa mokgwa wa tlwaelo wa mekgwa ya histoloji bakeng sa ho hlaselwa ha disele tsa masole a mmele le boitwanelo ba letlalo. Ho fapana ha boitwanelo ba masole a mmele kgahlano le hlongwa ke mekgasa ha mefuta ya dinku ho ile ha hlahlojwa. Ho bile le phapano pakeng tsa ho longwa le ho fodisa ho longwa boemong ba diphetoho tse ngata tsa letlalo haese mathata a mane a letlalo ho NA. Leha ho le jwalo, mefuta yohle ya dinku e bile le bokgafetsa ba bofokodi ba letlalo dibakeng tse lonngweng ke mekgasa. Dibaka tse hlasetsweng ke mekgasa di ne di na le hona ho kenelwa ke disele ka hare le hohle ho mefuta ya dinku. Mefuta ya NA le SAMM e bontshitse ho hlaselwa ha disele tse ikgethang tsa leukocytes dibakeng tse lonngweng ke mekgasa ha ho bapiswa le Dorpers. Basophils, mast cells le eosinophils di fumanehile ka bongata dibakeng tse lonngweng ke mekgasa ho dinku tse tshehadi tsa NA ha ho bapiswa le Dorper le mefuta ya SAMM. Diphetho tsena di bontsha bohlokwa ba disele tsena ho dinku e le ho thibela tshwaetso ya mekgasa. Mefuta ya mekgasa e tshwaeditse ho batlisiswa ha neutrophils dibakeng tse hlaselwang e ho longwa ke mekgasa. Bong ba mekgasa, ho etsa disampole tsa sebaka esita le bong ba mekgasa, sebaka sa ho etsa disampole esita le ho thibelwa ha mekgasa, ha ho a ama palo ya disele tsa masole a mmele. Ho lokela ho etswe diphuputso tse ding hape ka mofuta o le mong wa mekgasa ka nako e le nngwe e le ho utlwisisa le ho tseba haholwanyane ka sekgahla sa mofuta oo wa mokgasa ho diphoofolo kapa dinku tsa mefuta e fapaneng. Ho ile ha etswa diteko tsa dijini tse hlano (18S, GAPDH, YWHAZ, B2M le SDHA) bakeng sa botsitso ba tsona. SDHA, YWHAZ le B2M e ne e le mehlala e mengata ka ho fetisisa ya dijini e kgothaleditsweng ke tshekatsheko ya geNorm bakeng sa ho rarolla tlhahiso le tlhakiso ya dijini letlalong la nku. Diphihlello tsena di tla thusa bakeng sa tlhahiso ya diphuputso tsa dijini bakeng sa ho longwa ke mekgasa le dibaka tse amehileng ho mefuta ya NA, Dorper le SAMM. Diphuputso tsena di hlakisa hore ha ho mofuta wa dijini o hlakisitseng hantle ho maemo a fapaneng a ho etsa diteko. Tlhahiso ya IL-1β, IL-8, CCL2 le CCL26 e lekantswe ka nako ya nnete ya qPCR. IL-1β le IL-8 di ne di hlahisitswe hantle haholo ho longweng ke mekgasa le dibaka tse lonngweng. Dinku tse tshehadi tsa NA di bontshitse IL-1β haholo dibakeng tse lonngweng ho feta Dorpers. Mofuta wa NA wa dinku o ne o na le hona ho phahamisa tlhahiso ya dijini tsa CCL2, CCL26 le IL-8 boemong ba ho longwa ke mekgasa ha ho bapiswa le dibaka tsa taolo ya phodiso ho feta mefuta e meng. Hona ho bontsha hore IL-1 β, CCL26 le IL-8 di ka bapala karolo ya bohlokwa tsa ba molemo bakeng sa ho thibela ho ba kotsing ha dinku ka lebaka la tshwaetso ya mekgasa. Phapano ya ho hlahiswa ha chemokines tse pedi pakeng tsa NA le SAMM le Dorper ho bolela hore mofuta wa NA o ne o ka hlola anti-chemokine ya mathe a mokgasa. Boitwanelo ba ULE of R. evertsi evertsi induced hypersensitivity bo mefuteng yohle. Mofuta wa kgale wa NA o bontshitse dikarabo tse matla, tsa ka potlako le tse diehisitsweng; ho feta mefuta ya kgwebo. Diphetho di bontsha hore boitwanelo ba disele tsa masole a mmele di hlasimolohile ho lwantsha tlhaselo ya mekgasa ho NA. Ho ka sebediswa hypersensitivity reaction e le phenotypic marker ho kgetha diphoofolo kapa mefuta ya ditswadiso tse itwanelang haholo kgahlano le ho longwa ke mekgasa. Ho a tsebahala hore diphuputso tsa diphephetso bakeng sa ho thusa twantsho ya pathogens di a hlahlojwa ho tswa maemong a boitshwaro le boiketlo. Mekgwa e sebedisitsweng mona e ka lokiswa, ya hlabollwa, e le ho thusa tekodiso ya nako le nako ya diphoofolo tsa bohlokwa le ka ntle le ho sebedisa mekgwa e phephetsang jwaloka ho dumella phephetso ya tlhaho ho eketseha ka nako ho bahlahlobuwa ba kgethilweng. Ka kakaretso, diphuputso tsa karolo di behile ka hara patlisiso kutlwisiso e eketsehileng ya ovine tick-host interactions le dintlha tse bakang phapano ya bongata ba mekgasa. ___________________________________________________________________

𝑰𝒔𝒊𝒁𝒖𝒍𝒖 Ucwaningo luphenye imingcele yofuzo kanye nezimpendulo zezivikeli mzimba ekuhlaselweni kwemikhaza ezimfuyweni ezintathu zezimvu zaseNingizimu Afrikha (i-Namaqua Afrikaner [NA], i-Dorper kanye ne-SA Mutton Merino [SAMM]). Ucwaningo luhlose ukulinganisa imingcele yofuzo kanye ne-crossbreeding yesibalo somkhaza (TC) nesisindo sokulunyulwa (WW), ukuhlola umlando wokunamathiselwe komkhaza nezingosi zokulawula, ukukhetha izakhi zofuzo zokulinganisa idatha yokuvezwa kofuzo kulolu cwaningo, ukuze kuqhathaniswe isakhi se-cytokines. Inkulumo endaweni enamathiselwe umkhaza nokulawula amasayithi futhi ekugcineni ukuqhathanisa ukusabela kwe-hypersensitivity kwe-cutaneous nezibungu ezingaphekiwe (ULE) ze-Rhipcephalus evertsi evertsi phakathi kwezimvu ze-NA, i-Dorper ne-SAMM. Izilinganiso zofuzo ze-WW kanye ne-TC zalinganiselwa kusetshenziswa idatha yamawundlu anakekelwa e-Nortier Research Farm kusukela ngo-2010 kuya ku-2015. Okokuqala, idatha yamawundlu athengiswayo e-Dorper kanye namawundlu e-SAMM yahlanganiswa nedatha yeziphambano zawo ezihambisanayo ukuze kuhlolwe imiphumela yohlobo lwezilwane kanye nomthelela ongaba khona wamawundlu. ukwehluka kwezakhi zofuzo okungezona okungeziwe ku-WW ne-TC. Ohlaziyweni lwesibili, idatha yamawundlu e-Dorper athengisayo ahlanganiswe nedatha ye-NA engathuthukisiwe, yomdabu kanye nesiphambano se-NA x Dorper. Ekuhlaziyeni kokuqala i-coefficient of variations (CV) ibingu-24%, 95% kanye no-50% we-WW, i-TC ephelele engashintshiwe kanye ne-square root eguqule i-TC iyonke, ngokulandelana. I-Genotype ithinte i-WW kodwa hhayi i-TC. Isilinganiso se-heterosis esingaba ngu-4% satholwa ku-WW. Isilinganiso sesici esisodwa esingu-h² se-TC sasingu-0.11 ± 0.09. Imodeli ehlaziya yonke i-genotype h² iveze isilinganiso esingaphansi kancane sika-h² esingu-0.08 ± 0.07. Ekuhlaziyeni kwesibili i-CV ibingama-27% kanye nama-55% ku-WW kanye ne-square root iguqule ingqikithi ye-TC, ngokulandelana. I-WW ne-TC zathintwa i-genotype. I-WW ibonise i-heterosis efinyelela ku-8.5% kuyilapho inani elihambisanayo le-TC lifinyelela ku-23%. Isilinganiso sesici esisodwa esingu-h² se-TC sasingu-0.06 ± 0.05. Imodeli ehlaziya i-genotype h² yonkana iveze isilinganiso esiphezulu kakhulu se-h² esingu-0.27 ± 0.07. Le miphumela iphakamisa ukuthi ukuhlukahluka kofuzo ku-TC kwakuhlotshaniswa ngokuyinhloko nomehluko phakathi kwamaqembu ofuzo kuyilapho umehluko phakathi kwezilwane ngazinye phakathi kwamaqembu ofuzo ubungabalulekile kangako. Izilinganiso ze-Heterosis ze-WW zaziguquguquka phakathi kokuhlaziywa okubili, kodwa ngaphakathi kwezigaba ezibikwe ezincwadini. Lolu cwaningo lusungule ukuhluka okubalulekile ku-TC phakathi kwezinhlobo zezimvu lapho uhlobo lomdabu lwe-NA lwakha ingxenye yokuhlaziya. Isiphambano se-NA x Dorper sifane nohlobo lwe-Dorper oluthuthukisiwe lwe-WW kodwa i-NA engathuthukisiwe, ekwazi ukumelana ne-TC futhi ibonise amazinga abalulekile e-heterosis kuzo zombili izici. Izinsiza zofuzo zomdabu ze-ovine zingaba usizo ekuhlinzekeni ngezakhi zofuzo zezici eziguquguqukayo ezindaweni ezisengozini yamazinga aphezulu okuhlasela kwemikhaza. Ucwaningo olwengeziwe luyadingeka ukuze kucaciswe iqhaza elingadlalwa izinsiza zofuzo zomdabu zomvini ezinhlelweni ezididiyelwe zokulawula umkhaza ngaphansi kwezimo ezibonakala ngamazinga aphezulu enselelo yomkhaza. Ucwaningo lwe-histological lwenziwa ukuze kuhlolwe izici ze-histological ezindaweni ezinamathiselwe umkhaza kanye nokulawula izindawo ezifuyweni ezihlanzekile. Ama-skin biopsies ahlolwe kusetshenziswa amasu ajwayelekile e-histological ekungeneni kwamangqamuzana e-immunology kanye nokusabela kwesikhumba. Ukwehluka okuphawulekayo ekuphenduleni kwe-immunology ekunamathiselwe komkhaza ngaphakathi naphakathi kwezinhlobo zezimvu kwabonwa. Kube nomehluko phakathi kokunamathiselwe kanye nezingosi zokulawula eziningi zezinguquko zesikhumba (amaphutha) ngaphandle kweziphambeko ezine zesikhumba ku-NA. Kodwa-ke, zonke izinhlobo zazinezikhathi ezifanayo zokukhubazeka kwesikhumba ezindaweni zokunamathisela imikhaza. Izingosi ezinamathiselwe umaka maningi amathuba okuthi zingenwe amaseli ngaphakathi kanye nakuzo zonke izinhlobo zezinhlobo. Izinhlobo ze-NA kanye ne-SAMM zivame ukukhombisa ukungena okukhulu kwamaseli ama-leukocyte athile ezindaweni zokunamathisela umkhaza uma kuqhathaniswa ne-Dorpers. Ama-basophil, ama-mast cell kanye nama-eosinophil ayelokhu eqashelwa ngokwandayo endaweni enamathiselwe umkhaza emazinyaneni e-NA uma kuqhathaniswa ne-Dorper futhi, ngezikhathi ezithile, izinhlobo ze-SAMM. Le miphumela iphakamisa ukubaluleka kwala maseli ekumelaneni nezimvu ekuthelelekeni kwemikhaza. Uhlobo lwamazeze lube nomthelela ekubuthweni kwama-neutrophil ukuze kuphawulwe izindawo ezinamathiselwe. Ubulili bomaka, indawo yesampula kanye nezinga lokungena komkhaza akuzange kuthinte inani lamaseli amasosha omzimba. Ucwaningo olwengeziwe kufanele lwenziwe ngohlobo lomkhaza owodwa ngesikhathi ukuze kuqondwe kangcono umthelela oqondene nohlobo oluthile lokunamathela komkhaza ezilwaneni zezinhlobo zezimvu ezihlukene. Izakhi zofuzo ezinhlanu (18S, GAPDH, YWHAZ, B2M kanye ne-SDHA) zihlolelwe ukuzinza kwazo. I-SDHA, i-YWHAZ kanye ne-B2M bekuyizakhi zofuzo eziyisithenjwa ezifanele kakhulu ezinconywe ukuhlaziya kwe-geNorm ukuze kujwayeleke idatha yokuvezwa kofuzo esikhumbeni sezimvu. Lokhu okutholakele kuzosiza ekwenzeni idatha kujwayeleke ezifundweni zokukhuluma ngezakhi zofuzo ezindaweni ezinamathiselwe imikhaza kanye nokulawula iziza ze-NA, iDorper kanye ne-SAMM. Lolu cwaningo luphakamise ukuthi asikho isakhi sofuzo esiyinkomba esivezwa ngokuzinzile ezimeni ezihlukene zokuhlola. Isisho se-IL-1β, IL-8, CCL2 ne-CCL26 silinganiselwe ngesikhathi sangempela se-qPCR. I-IL-1β ne-IL-8 zivezwe kakhulu ekunamathiselwe umkhaza kunasezindaweni zokulawula. Izimvukazi ze-NA zizwakalisa i-IL-1β kakhulu ezindaweni ezinamathiselwe umkhaza kune-Dorpers. Uhlobo lwe-NA futhi lwalungase lulawule ukuvezwa kofuzo lwe-CCL2, CCL26 kanye ne-IL-8 ezindaweni ezinamathiselwe imikhaza uma kuqhathaniswa neziza zokulawula kunezinye izinhlobo. Lokhu kubonisa ukuthi i-IL-1 β, CCL26 kanye ne-IL-8 ingase ibe nengxenye ekuphikiseni noma ekululameni kwezimvu ekuhlaselweni kwemikhaza. Umehluko ekubonisweni kwama-chemokine amabili phakathi kwe-NA engazweli kanye ne-SAMM esengozini kakhulu kanye ne-Dorper usikisela ukuthi uhlobo lwe-NA lungakwazi ukunqoba umsebenzi wokulwa ne-chemokine wamathe omkhaza. I-ULE ye-R. evertsi evertsi ibangele ukusabela kwe-hypersensitivity kuzo zonke izinhlobo. I-NA yomdabu ibonise ukusabela okuqinile, ngokushesha nokubambezeleka, kunezinhlobo ezithengiswayo. Imiphumela iphakamisa ukuthi izimpendulo zamasosha omzimba zisetshenziswa ukuze kuliwe nokuhlasela kwemikhaza e-NA. Ukusabela kwe-hypersensitivity kungase kusetshenziswe njengomaka we-phenotypic ukukhetha izilwane noma izinhlobo ezimelana kakhulu nemikhaza. Kwaziwa kahle ukuthi ucwaningo olusekelwe enseleleni yokukhuthaza ukumelana namagciwane luyacutshungulwa ngokombono wesimilo kanye nenhlalakahle. Izindlela ezisetshenziswa lapha zingathuthukiswa ukuze kuvunyelwe ukuhlolwa okujwayelekile kwezilwane ezibalulekile ngaphandle kokusebenzisa amasu ahlaselayo, njengokuvumela inselele yemvelo eyanele ukuba iqongelele ngokuhamba kwesikhathi kumakhandidethi okukhetha. Sekukonke, ucwaningo lwengxenye olubikwe kulo mqulu lukhulise ukuqonda kwamanje ukusebenzisana kwe-ovine tick host kanye nezici ezinomthelela ekudaleni umehluko emithini yemikhaza. ___________________________________________________________________
Thesis (Ph.D.(Animal, Wildlife and Grassland Sciences))--University of the Free State, 2016
Keywords: Ticks -- Control; Insects pests; Livestock -- Parasites; Tick-borne disease in animals; Sheep -- Parasites; Dorper sheep -- South Africa; Merino sheep -- South Africa; Ticks as carriers of disease